P234 Changing natural history in IBD – steroid-free remission and surgery in two cohorts (≤2009 and > 2009) – an interplay between disease pattern, biologics and adherence. (16th January 2018) - Viola, A; Naim, M; Scolaro, M; Pinto-Vraca, T; Belvedere, A; Pisana, V; Costantino, G; Alibrandi, A; Fries, W
Abstract: Background: With the more frequent use of Biologics (BIO) a change in disease outcome for both, Crohn's disease (CD) and ulcerative colitis (UC), is expected but studies yield conflicting results. The aim of the present single centre study was to investigate changes of therapeutic approach, patients' adherence, and disease outcomes, i.e. steroid-free remission and surgery rates, in two IBD cohorts. Methods: we retrospectively assessed demographic (age, gender, smoking status) and disease-related data (disease, age at diagnosis, Montreal classification of IBD, disease pattern (DP)(1: onset and subsequent mild course, 2: relapsing, 3: chronic active disease), type and start of therapy, surgery rates, steroid free remission at 1 and 2 years after taking in charge, and patients' adherence) of patients followed at our IBD-UNIT. The patients were divided into two cohorts those taken over ≤ year 2009 and those taken over after year 2009). Results: cohort 1: 129 UC, 154 CD; cohort 2: 200 UC, 170 CD. In cohort 2, compared with cohort 1, there was a significant increase in steroid-free remission at year 1 ( p < 0.008) and 2 ( p < 0.041) in CD and in UC ( p < 0.022 and 0.048, respectively)(Figure 1). In CD, there was a significant reduction in surgery rates (19% vs. 11%, p < 0.006). UC colectomies were very low in both cohorts. While the use of immunomodulators (IMM) was comparable in both cohorts, BIO were earlier employed in cohort 2 (log-rank: p < 0.0001). By multivariate analysis, steroid free remission at 1 year was associated with DP-1 ( p = 0.047) and adherence ( p = 0.03), whereas steroid free remission at year 2 was associated with BIO use ( p = 0.000) and DP-1 ( p = 0.048). Adherence was associated with the use of IMM ( p = 012), BIO ( p = 0.000), and DP-1 ( p = 0.01). Conclusions: adherence, BIO, and disease pattern were associated with steroid-free remission at year 1 and 2. Reaching early benefit may influence patients' confidence and, thus, adherence. This in turn leads to better long-term results at least in patients with milder disease patterns.